A call to duty : a novel of the honorverse - Weber, David, 1952- (Weber, David, 1952- Manticore Ascendant, 2014)
"Growing up, Travis Uriah Long yearned for order and discipline in his life...two things his neglectful mother couldn't or wouldn't provide. So when Travis enlists in the Royal Manticoran Navy, he thought he'd finally found the structure he'd always wanted so desperately. But life in the RMN isn't exactly as expected. Boot camp is rough; his first ship assignment lax and disorderly; and with the Star Kingdom of Manticore still recovering from a devastating plague, the Navy is on the edge of extinction. The Star Kingdom is a minor nation among the worlds of the Diaspora, its closest neighbor months away and with little resources. With only modest interstellar trade, no foreign contacts to speak of, a plague ravaged economy and no enemies looming at the hyper limit, factions in Parliament want nothing more than to scrap the Navy and shift its resources elsewhere. But those factions are mistaken. The universe is not a safe place as Travis is about to find out"--